Sparse Array Optimization Using Simulated Annealing and Compressed Sensing for Near-Field Millimeter Wave Imaging - Gonzalez-Valdes, Borja; Allan, Gregory; Rodriguez-Vaqueiro, Yolanda; Alvarez, Yuri; Mantzavinos, Spiros; Nickerson, Matt; Berkowitz, Ben; Martinez-Lorenzo, J. A.; Las-Heras, Fernando; Rappaport, Carey M. (IEEE transactions on antennas and propagation, 2014)
The optimization and use of a sparse array configuration for an active three dimensional (3D) millimeter wave imaging system for personnel security screening is presented in this work. The combination of the optimization procedure with the use of Compressed Sensing techniques allows drastic reduction in the number of sensors, thereby simplifying the system design and fabrication and reducing its cost. Representative simulation results showing good performance of the proposed system are provided and supported by sample measurements.